Protection of Outsourced Labor in Indonesia: Political Law and Contemporary Islamic Law - Rodhotun Nimah; Imam Sya’roni; Suud Sarim Karimullah (BAYAN: Jurnal Studi Islam dan Humaniora, 2026)
This article discusses the welfare and protection of workers with an outsourcing system in terms of the contemporary Islamic law maqashid sharia. Based on the provisions in Article 66 of Regulation No.11 of 2020 on Job Creation, it is no longer stated regarding the limitations of work that are prohibited from being carried out by workers with an outsourcing system. The provisions in Regulation Number 11 of 2020 on Job Creation allow for no time limit for outsourced workers, so workers can be outsourced indefinitely, even for life. This protection is carried out before, during and after work. This research is normative legal research using a statutory approach as well as a review of Islamic law which uses literature study as a data collection method and is analyzed through an analytical descriptive method. The provisions in Law Number 11 of 2020 concerning Job Creation allow for no time limit for outsourced workers, so workers can be outsourced indefinitely, even for life. Based on the maqashid sharia of the Minister of Manpower Regulation No. 11 of 2020 concerning Job Creation related to the protection of labor, the outsourcing system is not in accordance with the indicators in the contemporary maqashid al-syari'ah which is based on sustainable justice by paying attention to aspects of social welfare and poverty elimination.